2017
DOI: 10.4085/1052-6050-51.6.06
|View full text |Cite
|
Sign up to set email alerts
|

Rest and Return to Activity After Sport-Related Concussion: A Systematic Review of the Literature

Abstract: Our main findings suggest that rest is underused by health care providers, recommendations for rest are broad and not specific to individual patients, an initial period of moderate physical and cognitive rest (eg, limited physical activity and light mental activity) may improve outcomes during the acute postinjury phase, significant variability in the use of assessment tools and compliance with recommended return-to-activity guidelines exists, and additional research is needed to empirically evaluate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 65 publications
1
62
0
2
Order By: Relevance
“…1 Previous reasoning behind rest was that it reduced the risk for subsequent concussion 2 and reduced potential stresses on the brain to promote recovery. 3 However, recent systematic reviews 4,5 determined that the extended rest may not be beneficial to patients, and moderate activity levels and early activity may help to decrease the risk of postconcussion syndrome and improve symptom duration. 6 Furthermore, recent statements have proposed a framework for more active treatments targeting specific clusters of symptoms following concussion to decrease comorbidities and day-to-day symptoms.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…1 Previous reasoning behind rest was that it reduced the risk for subsequent concussion 2 and reduced potential stresses on the brain to promote recovery. 3 However, recent systematic reviews 4,5 determined that the extended rest may not be beneficial to patients, and moderate activity levels and early activity may help to decrease the risk of postconcussion syndrome and improve symptom duration. 6 Furthermore, recent statements have proposed a framework for more active treatments targeting specific clusters of symptoms following concussion to decrease comorbidities and day-to-day symptoms.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…However, recent research has been unable to provide evidence to support the use of complete rest in the management of concussion beyond the acute phase following injury 3 , 14 , 15 . Three systematic reviews concluded that physical and cognitive rest may only be of use in the acute phase after concussion; however, they all found the evidence to be low level and inconclusive 3 , 14 , 15 . One review, focused on children, found that rest beyond the acute period may prolong symptoms 14 .…”
Section: Boxmentioning
confidence: 99%
“…Evidence does not support that rest beyond this period improves recovery; in children, prolonged rest may prolong symptoms 3,14,15 New recommendation: light intensity activity beyond initial period until the resolution of symptoms Consensus statement supports early introduction of symptom-limited physical activity if appropriate, although the evidence is not strong 3 the past 4 years. 2 Previously, consensus opinion recommended complete rest until the resolution of symptoms as the cornerstone of concussion management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging literature has indicated that prolonged periods of physical rest may be detrimental to SRC symptom recovery. 3,4 Physical activity during the subacute phase (≥ 6 weeks following diagnosis) has been explored as a potential intervention to facilitate physical and psychological recovery from SRC as well as to improve academic outcomes in young athletes experiencing prolonged recovery. 5 Though several governing bodies 1,2 have recommended cognitive and physical rest following SRC, it is imperative for researchers to investigate viable post-concussion treatment strategies to appropriately manage symptoms and facilitate positive outcomes following SRC in the acute phase.…”
mentioning
confidence: 99%